1990
DOI: 10.1136/jcp.43.6.508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an immunochemical assay for plasma fibrinogen and a turbidimetric thrombin clotting technique to discriminate hyperlipidaemic patients from healthy controls.

Abstract: Plasma samples from patients attending a lipid clinic (n = 14) and healthy control subjects (n = 21) were assayed for fibrinogen using an immunochemical method (radial immunodiffusion) and a turbidimetric assay based on the thrombin clotting technique. The patients had significantly higher plasma fibrinogen concentrations than controls by both methods, but there was significant overlap between the two groups when fibrinogen was assayed by the thrombin clotting technique; there was almost complete separation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Recently, the immunologic determinations of fibrinogen concentration have been proven to be superior to clotting techniques in predicting the incidence of ischemic heart disease 12 and in separating patients attending a lipid clinic from healthy controls. 45 Altogether, these observations might reflect a greater precision of nephelometric determinations of fibrinogen concentrations, different effects of and determinants for the hemostatic function of plasma fibrinogen as opposed to its rheological impact, or possibly an as-yetundetermined additional role of degradation products of fibrin and fibrinogen in the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the immunologic determinations of fibrinogen concentration have been proven to be superior to clotting techniques in predicting the incidence of ischemic heart disease 12 and in separating patients attending a lipid clinic from healthy controls. 45 Altogether, these observations might reflect a greater precision of nephelometric determinations of fibrinogen concentrations, different effects of and determinants for the hemostatic function of plasma fibrinogen as opposed to its rheological impact, or possibly an as-yetundetermined additional role of degradation products of fibrin and fibrinogen in the atherosclerotic process.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, with advances in surgical technique in the rectum, their surgeons will want to know about the radial margin of excision. 4 Marking the resection margin is not new, but marking with India ink is messy, allows only one colour, and has a habit of spreading all over the specimen, failing to confine itself to the true margins, and it takes a long time to dry. Our gelatin solution, originally devised for breast marking,5 dries instantly on contact with the tissue, does not run down tissue planes, is easily recognised microscopically, and permits differential colouring of the anterior, posterior, and the two lateral margins.…”
mentioning
confidence: 99%
“…However, other authors [14] have reported IFg levels significantly lower than functional Fg levels in several samples both from healthy subjects and patients. It should be stressed that problems of accuracy exist for the most widely employed fibrinogen assays at least in part due to insufficiently pre cise calibration procedures [9,11], We know that CFg/IFg ratios markedly higher than 1 are inaccurate by definition and are probably the result of some aberration.…”
Section: Discussionmentioning
confidence: 84%